Facing Mpox (Former Monkeypox) in Latin America: The Example of Peru and Its Vulnerable Healthcare System - Al-kassab-Córdova, Ali (2023)
The new outbreak of monkeypox, a viral zoonotic disease, has affected more than 82,500 people and at least 110 countries worldwide as of 14 December 2022, with 81,580 people affected in 103 non-endemic areas of Africa [1]. The monkeypox virus is a DNAOrthopoxvirus that is part of the variola virus family (Poxviridae), which causes Citation: Al-kassab-Córdova, A.; Ulloque-Badaracco, J.R.; Benites-Zapata, V.A.; Sah, R.; Rodriguez-Morales, A.J. Facing Mpox (Former Monkeypox) in Latin America: The Example of Peru and Its Vulnerable Healthcare System. Vaccines 2023, 11, 10. https:// doi.org/10.3390/vaccines11010010 Received: 5 December 2022 Revised: 9 December 2022 Accepted: 14 December 2022 Published: 20 December 2022 Copyright: © 2022 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https:// creativecommons.org/licenses/by/ 4.0/). smallpox. Symptoms of monkeypox, however, are milder and rarely life-threatening. Recently, after a series of consultations with global experts, the World Health Organization (WHO)proposed “Mpox” as a new preferable term, replacing monkeypox [2]. The arrival of monkeypox to multiple regions, including Latin America, an area whose countries are primarily of low- and middle-income and that were severely affected by the SARS-CoV2/COVID-19 pandemic during 2020–2022, has raised the necessity of further preparedness to deal with a new epidemic, which was declared a Public Health Emergency of International Concern (PHEIC) by the WHO, on 23 July 2022 [3]. However, budget cuts and the structural deficiencies of the Latin American health systems pose additional challenges to dealing with this threat